Care and self-narrative: a philosophical view - Gorza, Monica (Medicina e Morale, 2023)
In his Confessions, Augustine returns to the topic of care several times. In the Book IX, care is not merely a literary motif, but a question that challenges philosophical reflection. With reference to some passages in which Augustin presents the biography of his mother, Monica, - already at the end of her life - this article aims to discuss the issue of care by interrogating the sphere of the narrative self developed by Paul Ricoeur, who worked at length on the theme of the constitution of personal identity through narration. In particular, my attention will focus on the notion of narrative identity in relation with the Ricoeurian conception of possibility. This article attempts to appreciate how Augustine's narrative and Ricoeur's reflections on narration can be interpreted in the light of the questions that animate the bioethical debate on the topics of care and personal identity bringing new mutually reflective insights